FENOMENA SOSIAL MITOS KALI PEMALI DI BREBES SEBAGAI SUMBER PEMBELAJARAN PKN DALAM MEMBENTUK CIVIC DISPOSITION SISWA SEKOLAH DASAR - Leni Yunitasari; Muhammad Iqbal Birsyada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the fact that Civic Education (PKn) learning in elementary schools tends to be theoretical and less contextual, resulting in the suboptimal development of students’ civic disposition. This condition highlights the need for innovative learning approaches that connect instructional content with students’ real-life social contexts. This study aims to analyze the social phenomenon of the Kali Pemali myth in Brebes Regency as a source of Civic Education learning in shaping elementary school students’ civic disposition. The research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation techniques. The findings reveal that the Kali Pemali myth contains social values relevant to civic character formation, including responsibility, environmental awareness, discipline, and adherence to social norms, as reflected in community behavior. The discussion indicates that integrating local myths into Civic Education learning enhances students’ understanding because it is contextual, closely related to their daily experiences, and supported by family and community environments. Furthermore, the use of local myths as learning resources not only enriches instructional materials but also serves as an effective strategy for internalizing civic values. In conclusion, local myths can function as an innovative alternative in Civic Education learning to foster students’ civic disposition in a more meaningful and contextual manner.